2014
DOI: 10.1073/pnas.1402814111
|View full text |Cite|
|
Sign up to set email alerts
|

Novel coding, translation, and gene expression of a replicating covalently closed circular RNA of 220 nt

Abstract: The authors note, "Figs. 2, 3, and 5 were not in compliance with PNAS figure preparation policies because some gel lanes from noncontiguous experiments were spliced together. The corrected figures shown below have white spaces inserted to indicate noncontiguous experiments." Fig. 2. In vitro transcription/translation and immunoprecipitation of translated products using antiserum raised against the scRYMV ORF-encoded protein.(A) Lane 2 shows 19-kDa and 16-kDa proteins from reaction using pET52 DNA, whereas lane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(107 citation statements)
references
References 27 publications
3
102
0
Order By: Relevance
“…Early in 1998, Perriman et al reported that a circular mRNA containing a simple green fluorescent protein (GFP) open reading frame could direct GFP expression in Escherichia coli [16]. Subsequently, AbouHaidar et al discovered a circRNA (220 nt) of the virusoid associated with rice yellow mottle virus can code for a 16-kD protein [17]. It was shown that peptides can be translated from circRNAs in vitro [18] or in vivo [16], only when the RNAs contain internal ribosome entry site elements (IRES) [18] or prokaryotic ribosome-binding sites [16].…”
Section: Introductionmentioning
confidence: 99%
“…Early in 1998, Perriman et al reported that a circular mRNA containing a simple green fluorescent protein (GFP) open reading frame could direct GFP expression in Escherichia coli [16]. Subsequently, AbouHaidar et al discovered a circRNA (220 nt) of the virusoid associated with rice yellow mottle virus can code for a 16-kD protein [17]. It was shown that peptides can be translated from circRNAs in vitro [18] or in vivo [16], only when the RNAs contain internal ribosome entry site elements (IRES) [18] or prokaryotic ribosome-binding sites [16].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs are a class of covalently closed circular RNAs that have been originally identified in plant viroid [6, 7], virus [8, 9], archaea [10], and metazoans [11]. Unlike linear RNAs, circRNAs exhibit the remarkable characteristic of being covalently closed continuous loops without 5’ to 3’ polarity and without a polyadenylated tail [12], which allows circRNAs to resist the degradation of major RNA enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…Involving 64 nucleotide triplets called codons (Elzanowski and Ostell, 2013), the genetic code is a system coding the set of rules by which information is translated from RNA into proteins by living cells and viruses, by specifying which amino acid will be added during protein synthesis. Information encoded within genetic material also possesses superimposed cryptic messages (Popov et al, 1996), revealing highly complex semiotics (e.g., in circular virusoid RNAs, AbouHaidar et al, 2014). The rules of DNA punctuation vary among 25 recognized genetic codes, suggesting these constantly evolve.…”
Section: Introductionmentioning
confidence: 99%